Measurement invariance of the Positive Gains Scale in families of children with and without disabilities. (August 2020) - Jess, Mikeda; Bailey, Tom; Pit-ten Cate, Ineke M.; Totsika, Vasiliki; Hastings, Richard P.
Highlights: The study support internal consistency of the PGS across groups. Measurement invariance could not be established for PGS. Researchers should consider possible biases when using the PGS in case-control studies. Abstract: Background: Despite the high frequency of case-control studies in the developmental disability literature, there is a paucity of research establishing the measurement equivalence of instruments used, and particularly those relating to positive perceptions and experiences in family disability research. Aims: The present study sought to establish measurement invariance for the Positive Gains Scale (PGS) across 1219 mothers of children with developmental disabilities, 234 mothers of children with spina bifida/hydrocephalus, and 157 mothers of children without disabilities. Methods and procedures: A three-step test for measurement invariance across the three groups was conducted using Multigroup Confirmatory Factor Analysis. Outcomes and results: Loadings between the three groups were invariant, suggesting the criteria to assume metric invariance was met. However, the assumption of scalar invariance was not met, suggesting that item intercepts differed between the three groups. Conclusions and implications: Our findings suggest that the PGS cannot be meaningfully used to compare outcomes between mothers of children with developmental disabilities and other mothers. These findings may have wider implications for research utilising well-being measures to make comparisons with carers of children with developmental disabilities.